Anti-Influenza Hyperimmune Immunoglobulin Enhances Fc-Functional Antibody Immunity During Human Influenza Infection. (31st May 2018) - Vanderven, Hillary A; Wragg, Kathleen; Ana-Sosa-Batiz, Fernanda; Kristensen, Anne B; Jegaskanda, Sinthujan; Wheatley, Adam K; Wentworth, Deborah; Wines, Bruce D; Hogarth, P Mark; Rockman, Steve; Kent, Stephen J
Abstract : Anti-influenza hyperimmune immunoglobulin (Flu-IVIG) generally contained higher concentrations of influenza-specific Fc-functional antibodies than standard intravenous immunoglobulins against an array of influenza virus strains and subtypes. Passive infusion of Flu-IVIG into influenza-infected patients transiently boosted Fc-functional antibodies early after infusion. Abstract: Background: New treatments for severe influenza are needed. Passive transfer of influenza-specific hyperimmune pooled immunoglobulin (Flu-IVIG) boosts neutralizing antibody responses to past strains in influenza-infected subjects. The effect of Flu-IVIG on antibodies with Fc-mediated functions, which may target diverse influenza strains, is unclear. Methods: We studied the capacity of Flu-IVIG, relative to standard IVIG, to bind to Fcγ receptors and mediate antibody-dependent cellular cytotoxicity in vitro. The effect of Flu-IVIG infusion, compared to placebo infusion, was examined in serial plasma samples from 24 subjects with confirmed influenza infection in the INSIGHT FLU005 pilot study. Results: Flu-IVIG contains higher concentrations of Fc-functional antibodies than IVIG against a diverse range of influenza hemagglutinins. Following infusion of Flu-IVIG into influenza-infected subjects, a transient increase in Fc-functional antibodies was present for 1–3 days against infecting and noninfecting strains of influenza. Conclusions: Flu-IVIG contains antibodies with Fc-mediated functions against influenza virus, and passive transfer of Flu-IVIG increases anti-influenza Fc-functional antibodies in the plasma of influenza-infected subjects. Enhancement of Fc-functional antibodies to a diverse range of influenza strains suggests that Flu-IVIG infusion could prove useful in the context of novel influenza virus infections, when there may be minimal or no neutralizing antibodies in the Flu-IVIG preparation.